Cross-border governance in the European Union - Kramsch, Olivier Thomas, 1963-; Hooper, Barbara, 1945- (Routledge, 2004)
This book discusses and evaluates the problems of governance within the European Union's cross border regions from diversity of perspectives and over a range of selected case studies.
Keywords: European Union.; Regionalism (International organization); Regionalism (International organization) -- Case studies.; European Union countries -- Politics and government.; Régionalisme (Politique internationale); Régionalisme (Politique internationale) -- Études de cas.; LAW -- International.; Politics and government; European Union countries; Openbaar bestuur.; Euregio's.; Regionalisme.; Case studies